THE WAYS OF PROVIDING SOCIO- POLITIC AND SOCIAL SECURITY IN UZBEKISTAN - Pirnasarovich, Abulkasimov Khasan; Khasanovich, Abulkasimov Murad (International Journal of Psychosocial Rehabilitation, 2020)
The article covers the main points of social security and threats, also in the article are considered the features of ensuring social security in Uzbekistan